Unconjugated bilirubin as a state marker in patients with schizophrenia in acute episode: an Egyptian study - Abd-Elsamei, Afaf Mohamed; Gabry, Dina Aly El; Mohamed, Maha Sabry; Mohamed, Mariam Yehia; Serag, Rehab (Middle East Current Psychiatry, 2024)
Background There is a substantial body of evidence linking unconjugated bilirubin to schizophrenia. Most of the earlier research has found a statistically significant relationship between the two factors. Aim of the work To study the level of unconjugated bilirubin in individuals with acute schizophrenia and to investigate its correlation with neuropsychological, psychopathological, and psychosocial aspects of the disorder. Patients and methods Eighty schizophrenia patients were included in the sample, they had multiple previous episodes and were in acute episodes at the time of recruitment. Forty healthy individuals were recruited for the control group. The DSM-IV was used to diagnose the subjects, and the Trail Making Test (TMT), Positive and Negative Syndrome Scale (PANSS), General Assessment of Function (GAF), and Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) were used to evaluate the subjects’ social functioning, symptom severity, and cognitive functioning. A blood sample was drawn to measure serum bilirubin level. We analyzed the relationship and correlation of unconjugated bilirubin with the previous scale scores. Results Compared to healthy control individuals, who volunteered to participate, schizophrenia patients reported significantly higher levels of both total and indirect bilirubin. One subject (with schizophrenia) had an abnormally elevated total bilirubin level (> 1.2 mg/dL). Neither the direct nor the indirect bilirubin levels (> 0.3 mg/dl or > 1.2 mg/dL) were clinically abnormal in any of the patients. PANSS total score, PANSS N score, and PANSS G score were found to have a statistically significant positive connection with levels of total, direct, and indirect bilirubin. Age, gender, smoking, BMI, Total PANSS, PANSS P, PANSS N, PANSS G, GAF, TMT-A, TMT-B, antipsychotic medication, psychotic disorder duration, and duration of untreated psychosis were not predictive of total or indirect bilirubin levels, according to linear regression analysis. However, Total PANSS, PANSS N, and PANSS G were significantly predictive for direct bilirubin levels. Conclusion A statistically significant difference in total and unconjugated bilirubin mean serum levels between schizophrenia patients and healthy individuals was found. More studies are recommended to revise the contradictory results in literature on the unconjugated bilirubin and Schizophrenia.